Comparative Study on the Adsorption Capacity of Activated Carbon Prepared from Lapsi Seed Stone and Betel nut using Phosphoric Acid - Joshi, Sahira (Journal of the Institute of Engineering, 2018)
This paper presents the comparative study on the adsorption capacity of activated carbons prepared from Lapsi (Choerospondias axillaris) seed stone and Betel (Areca catechu) nut. Activated carbons (ACs) were prepared from Lapsi seed stone (LSS) and Betel Nut (BN) by chemical activation with H3PO4 (in the ratio of 1:1 by weight) at 400°C. The pore structure of activated carbons was determined by iodine number and methylene blue number. Surface morphology of ACs was studied by scanning electron microscopy (SEM). Surface functional groups were analyzed by Fourier Transform Infra Red Spectroscopy (FTIR). As indicated by TGA analysis, the appropriate temperature required for carbonization was 400 ºC. Betel nut AC showed high iodine number and methylene number of 888 mg/gm and 369 mg/gm respectively. SEM micrographs of Betel nut AC show the presence of well developed pores on its surface. FTIR result indicated that both ACs contain −OH, >C=O groups as oxygen containing surface functional groups. Based on the result, the AC prepared from betel nut by activation with H3PO4 is comparable with commercial activated carbon and could be used as potential adsorbent for removal of pollutants from water and waste water. Journal of the Institute of Engineering, 2017, 13(1): 153-159